Perbedaan Pelepasan Ion Nikel (Ni) dan Kromium (Cr) Kawat Ortodonti Stainless Steel pada Perendaman Pasta Gigi Ortodonti dan Non-Ortodonti - Wondal, Loisaviny H. D.; Anindita, P. S.; Tambunan, Elita (e-GiGi, 2018)
Abstract: Recently, orthodontic toothpaste with colostrum has been introduced which is different from non-orthodontic toothpaste. Albeit, orthodontic and non-orthodontic toothpastes contain citric acid and some kinds of sodium compounds that can initiate corrosion of stainless steel orthodontic archwire indicated by the release of nickel and chromium ions. This study was aimed to determine the difference in nickel and chromium ion releases from the stainless steel orthodontic archwires immersed in artificial saliva plus orthodontic toothpaste or non-orthodontic toothpaste. This was a true experimental study with a post-test only control group design. Samples were stainless steel orthodontic archwires immersed in artificial saliva plus orthodontic toothpaste or non-orthodontic toothpaste. Released nickel and chromium ions were analyzed with atomic absorption spectrometer (AAS). In both treatment groups (orthodontic and non-orthodontic pastes), the independent t-test showed that the P value of released nickel ions was 0.572 and of released chromium ions was 0.059 (P >0.05). Conclusion: There were no significant differences between the release of nickel and chromium ions of stainless steel orthodontic archwires immersed in artificial saliva plus orthodontic toothpaste and in artificial saliva plus non-orthodontic toothpaste.Keywords: stainless steel orthodontic archwire, nickel and chromium ion, orthodontic and non-orthodontic toothpaste.Â Abstrak: Dewasa ini sudah tersedia pasta gigi ortodonti dengan kandungan colostrum yang membedakannya dengan pasta gigi non-ortodonti. Pasta gigi ortodonti dan non-ortodonti mengandung citric acid dan beberapa jenis senyawa sodium yang dapat memicu terjadinya korosi pada kawat ortodonti stainless steel yang ditandai dengan pelepasan ion nikel dan kromium. Penelitian ini bertujuan untuk mengetahui apakah terdapat perbedaan jumlah pelepasan ion nikel dan kromium kawat ortodonti stainless steel yang direndam dalam pasta gigi ortodonti dan non-ortodonti. Jenis penelitian ialah eksperimental murni dengan post-test only control group design. Sampel yang digunakan yaitu kawat ortodonti stainless steel yang direndam dalam saliva artifisial ditambahkan pasta gigi ortodonti atau yang non-ortodonti. Pelepasan ion nikel dan kromium dianalisis menggunakan Spektrometri Serapan Atom (SSA). Hasil uji t tidak berpasangan pada kelompok perlakuan baik larutan pasta gigi ortodonti maupun yang non-ortodonti menunjukkan pelepasan ion nikel dengan P=0,572 dan pelepasan ion kromium dengan P=0,059 (P >0,05). Simpulan: Tidak terdapat perbedaan bermakna pelepasan ion nikel dan kromium pada kawat ortodonti stainless steel yang direndam dalam saliva artifisial ditambahkan pasta gigi ortodonti dibandingkan pasta non ortodonti.Kata kunci: kawat ortodonti stainless steel, nikel, kromium, pasta gigi ortodonti dan non ortodonti